Analysis for Identification of Distinct and Uniform Extant Jute (Corchorus olitorius L. and C. capsularis L.) Varieties - D. KUMAR,; R.C. AGRAWAL,; T. BEGUM, (Seed Research, 2026)
In the present era of Intellectual Property Rights, the distinctiveness, uniformity and stability of a candidate variety are the basis for granting protection of Plant Breeder's Rights. Keeping this in view, 27 jute varieties were characterized for 5 quantitative characters viz. leaf angle, time of 50 per cent flowering, plant height, days to maturity and 1000 seed weight, prescribed in the Draft National DUS Test Guidelines of Jute. On the basis of COYD and COYU analysis of 5 quantitative characteristics, distinctiveness and uniformity of 3 olitorius varieties viz. JRO 3690, Chinsurah Green and JRO 36E at CRIJAF, Barrackpore location and 4 varieties TJ 40, Chinsurah Green, Bidhan Rupali and JRO 36E at CSRSJAF, Budbud location could be established whereas 6 capsularis varieties (JRC 212, JRC 7447, JRC 321, JRC 4444, UPC 94 and Bidhan Pat 2) at CRIJAF, Barrackpore location and only 1 variety, JRC 321 at CSRSJAF, Budbud location was ascertained.